ANALISIS USAHA AGROINDUSTRI TAHU (STUDI KASUS PADA USAHA AGROINDUSTRI TAHU BAPAK HENRY DI DESA PANDAN WANGI KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU) - Muhammad Afiq; Eliza Eliza; Deby Kurnia (Indonesian Journal of Agricultural Economics, 2019)
The purpose of this research is to know and analyze the financial feasibility and sensitivity level of tofu agroindustry Mr. Henry in Pandan Wangi Village Indragiri Hulu Regency. This study uses case study method and the number of respondents at agroindustry Mr. Henry in Pandan Wangi Village Indragiri Hulu Regency. The financial feasibility analysis of tofu agroindustry using investment criteria, such as: Net Present Value (NPV), Net Benefit-Cost Ratio (Net B / C), Internal Rate of Return (IRR), and Payback Period (PP). The result of the research shows that agroindustry business is feasible to be developed based on its investment criteria, which shows that NPV (positive) is Rp.121.502.767, Net B / C is 4.72 (Net B / C> 1), IRR is 89.97 % (IRR> DF 12%), and PP for 3 years 3 months, which means the business has been able to cover the investment cost before the end of business. Sensitivity analysis can be concluded that soybean increasing price by 4% effort still feasible because NPV (positive), Net B / C> 1, IRR> 12%, and PP for 7 years, while at soybean price rose by 5% and 61%, Business is not feasible because NPV (negative), Net B / C <1, IRR = 12%, and PP cannot cover investment cost before the end of business. A 10% reduction in production scale business is not feasible because NPV (negative), Net B / C <1, IRR <12%, and PP cannot cover the investment cost before the end of the business ends.